Paraoxonase 1 activity in endocrine diseases [Endokrin hastalıklarda paraoksonaz 1 enzim aktivitesi] - (:unkn) unknown (Turkiye Klinikleri, 2011)
Paraoxonase is an esterase bound to high-density lipoproteins which by metabolizing lipid peroxides, prevents their accumulation on low-density lipoproteins. It also hydrolyzes various organophosphorus compounds. Considering the role of PON1 in hydrolyzing phospholipids and cholesteryl-ester hydroperoxides and thus protecting lipoproteins against oxidative modification, it can be concluded that PON1 may be an indicator of the risk of atherosclerosis/coronary artery disease development. Recent studies have also shown that PON activity was related to several disorders, including endocrine disorders as well. In this paper, we review the relation of PON1 activity with endocrine diseases like diabetes, thyroid dysfunction, osteoporosis, polycystic ovary syndrome (PCOS), obesity and dyslipidemia.
Keywords: Acromegaly; Diabetes; Dyslipidemia; Endocrine disorders; Obesity; Paraoxonase 1; PCOS; PON1